The impact of Montessori method on early mathematical competence of young children - Siaviki, Athanasia; Tympa, Eleni; Karavida, Vasiliki; Fykaris, Ioannis (Intelektual Pustaka Media Utama, 2025)
The Montessori method offers an alternative approach to public and independent schooling. In the Greek educational system, the Montessori method is mainly applied in preschool and primary educational contexts. The main research objective was to investigate the early mathematical competence of students aged 4-7 years old attending a Montessori preschool educational center with those of students aged 4-7 years old attending educational institutions where traditional teaching techniques and methods are being implemented at the Eastern Thessaloniki, Greece. The overall research sample was 142 students, 68 taught in the Montessori institution and 74 attending typical ones, as well as 119 parents of the children that were measured. A questionnaire was administered electronically to the parents that agreed to participate in the research, while the measurements of the early mathematical competence were carried out via the Utrecht Early Mathematical Competence Scales. Overall findings showed that the scores of the students attending the Montessori educational institution were higher than those of the ones attending typical educational institutions, especially those of pre-kindergarten, kindergarten and first grade children.